Analysis of Work Ethic and Work Discipline on Employee Performance with Competence as an Intervening Variable in State Civil Apparatus in Medan Baru District - Sarinah Pohan; Wilchan Robain; Sri Rahayu (Yayasan Multidimensi Kreatif, 2024)
This research was carried out to see the influence of Work Ethic and Work Discipline on the performance of employees with competence as an intervening variable in the State Civil Apparatus in Medan Baru District, this study uses the analysis path model with the smart PLS measurement method version 3.3.3. Data collection is carried out by giving questionnaires to respondents, this type of research uses the type of quantitative research and primary data sources as the data source. The results of this study are as follows: Work Discipline has a positive and significant effect on Employee Performance with the original sample value of 0.427 and p value of 0.006. Work Discipline had a positive and significant effect on Competence with an original sample value of 0.756 and a p value of 0.000. Work Ethic had a positive and significant effect on Employee Performance with the original sample value of 0.267 and p value of 0.006. Work Ethic had a positive and significant effect on Competence with an original sample value of 0.234 and a p value of 0.000. Competencies that had a positive effect were not significant in Employee Performance with an original sample value of 0.277 and a p value of 0.059. Work Discipline has a positive and insignificant effect on Employee Performance indirectly through Competency with an original sample value of 0.209 and a p value of 0.059. Work Ethic has a positive and insignificant effect on Employee Performance indirectly through Competency with an original sample value of 0.065 and a p value of 0.091.